Fraxetin Inhibits the Proliferation and Metastasis of Glioma Cells by Inactivating JAK2/STAT3 Signaling. (19th April 2021) - Qu, Liangchen; Lin, Pan; Lin, Minjie; Ye, Shumin; Papa Akuetteh, Percy David; Youyou Zhu
Abstract : Glioma is the most common brain tumor and is characterized by high mortality rates, high recurrence rates, and short survival time. Migration and invasion are the basic features of gliomas. Thus, inhibition of migration and invasion may be beneficial for the treatment of patients with glioma. Due to its antitumor activity and chemical reactivity, fraxetin has attracted extensive interest and has been proven to be an effective antitumor agent in various cancer types. However, currently, the potential effects of fraxetin on glioma have not been investigated. Here, we demonstrate that fraxetin can inhibit the proliferation, invasion, and migration of glioma and induce apoptosis of glioma cells in vitro and in vivo . Therefore, these findings establish fraxetin as a drug candidate for glioma treatment. Furthermore, fraxetin was able to effectively inhibit the JAK2/STAT3 signaling in glioma. In summary, our results show that fraxetin inhibits proliferation, invasion, and migration of glioma by inhibiting JAK2/STAT3 signaling and inducing apoptosis of glioma cells. The present study provides a solid basis for the development of new glioma therapies.